Passaggi: esperienze transculturali nei servizi psichiatrici. Incontro con Alfredo Ancora - Ancora, Alfredo; Scarciglia, Miriam (Il sogno della farfalla, 2013)
The article offers a summary of a meeting held on 3.3.2012 at the Amore e Psiche bookshop in Roma with the psychiatrist Alfredo Ancora, whose starting point was his long experience as a transcultural psychiatrist and the work he has carried out with migrants in Roman psychiatric centres. The debate, organized by Miriam Scarciglia, revolves around encounters with and voyages into different worlds that foster processes of mutual change and affect, in the first instance, the individuals concerned. The interlocutors discuss their psychiatric experiences both in the public and private sphere finding agreement on the point that in transcultural clinical practice a different way of getting to know the other not involving a strictly rational approach is enhanced, entailing the development of sensitivity and empathetic communication.